111. Intraoperative neurophysiological monitoring of corticobulbar muscle motor evoked potentials in children younger than 2 years. Issue 4 (April 2016) - Tramontano, V.; Arcaro, C.; Basaldella, F.; Masotto, B.; Bricolo, A.; Squintani, G.; Sala, F.
Abstract : Corticobulbar muscle motor evoked potentials (CBT-mMEPs) monitoring is usually reported for the VII cranial nerve (CN) but rarely for the IX/X and XII CN, and its application is anecdotal in young children. We present three cases of children younger than 2 years operated on for brainstem tumour, with continuous monitoring of lower CN CBT-mMEPs. CBT-mMEPs were elicited by transcranial electrical stimulation at C3/Cz and C4/Cz using a train of 4 stimuli (ISI 2 ms, duration 0.5 ms each, at 1 Hz and intensity up to 200 mA). Recording hook-wire electrodes were placed in pharyngeal and hypoglossal muscles for the IX/X and XII CN respectively. In all patients CBT-mMEPs were stable throughout the entire surgical procedure with no changes in threshold intensity. Post-operatively, none of the children experienced significant tongue palsy or dysphagia/dysphonia. Therefore three true negative cases were observed. CBT-mMEPs of the lower CN is not of widespread use; in particular, there is virtually no report on the use of this technique in very young children where the incomplete myelination of motor pathways may impair a successful monitoring under general anaesthesia. CBT-mMEPs for the IX/X and XII CN is feasible and reliable even in children younger than 2 years.